High salinity slowed organic acid production from acidogenic fermentation of kitchen wastewater by shaping functional bacterial community. (15th May 2022) - Huang, Jianghao; Pan, Yu; Liu, Li; Liang, Jinsong; Wu, Linyu; Zhu, Hongtao; Zhang, Panyue
Abstract: The high salinity of kitchen wastewater might have adverse effects on the production of short-chain fatty acids (SCFAs) in anaerobic fermentation. The effects and mechanisms of salinity on SCFA production in the anaerobic fermentation of kitchen wastewater were studied by varying the salt concentration, as follows: 0 g/L (S0), 2 g/L (S2), 6 g/L (S6), 10 g/L (S10), 15 g/L (S15), and 20 g/L (S20). Experimental results showed that hypersaline conditions (>10 g NaCl/L) accelerated the release of soluble proteins at the initial stage of anaerobic fermentation. They also significantly prohibited the hydrolysis and degradation of soluble proteins and carbohydrates. Compared with low salinity tests, the SCFA concentrations under hypersaline conditions (>10 g NaCl/L) only reached approximately 43% of the highest concentration on day 10, although the SCFA concentrations in all tests were very close on day 10 (14 g COD/L). High salinity delayed the production of n-butyric acid but did not change the composition of the total SCFAs. High salinity enriched Enterococcus and Bifidobacterium, the relative abundance levels of which reached 27.57% and 49.71%, respectively, before the depletion of substrate. High salinity showed a negative correlation with the relative abundance of the genera Clostridium_sensu_stricto_1, Prevotella and unclassified_f_Oscillospiraceae which are responsible for SCFA production. This study provided a theoretical basis for the fficient utilization of kitchen wastewater. Graphical abstract: Image 1 Highlights: Salinity >10 g/L prohibited the bioconversion of proteins and carbohydrates. Hypersaline conditions enriched Enterococcus (27.57%) and Bifidobacterium (49.71%). Salinity >10 g/L retarded acidogenic fermentation. High salinity has more abundant metabolism functions predicted with PICRUSt.